EIL2 Transcription Factor and Glutathione Synthetase Are Required for Defense of Tobacco Against Tobacco Blue Mold - Orlando Borrás-Hidalgo; Bart P. H. J. Thomma; Cyrelys Collazo; Osmany Chacón; Carlos J. Borroto; Camilo Ayra; Roxana Portieles; Yunior López; Merardo Pujol (Molecular Plant-Microbe Interactions, 2006)
In order to identify tobacco (Nicotiana megalosiphon) genes involved in broad-spectrum resistance to tobacco blue mold (Peronospora hyoscyami f. sp. tabacina), suppression subtractive hybridization was used to generate cDNA from transcripts that are differentially expressed during an incompatible interaction. After differential screening by membrane-based hybridization, clones corresponding to 182 differentially expressed genes were selected, sequenced, and analyzed. The cDNA collection comprised a broad repertoire of genes associated with various processes. Northern blot analysis of a subset of these genes confirmed the differential expression patterns between the compatible and incompatible interaction. Subsequent virus-induced gene silencing (VIGS) of four genes that were found to be differentially induced was pursued. While VIGS of a lipid transfer protein gene or a glutamate decarboxylase gene in Nicotiana megalosiphon did not affect blue mold resistance, silencing of an EIL2 transcription factor gene and a glutathione synthetase gene was found to compromise the resistance of Nicotiana megalosiphon to P. hyoscyami f. sp. tabacina. Potentially, these genes can be used to engineer resistance in blue mold-susceptible tobacco cultivars.